A review of the biotransformations of priority pharmaceuticals in biological wastewater treatment processes. (1st January 2021) - Nguyen, P.Y.; Carvalho, Gilda; Reis, Maria A.M.; Oehmen, Adrian
Highlights: Biological & metabolic factors impacting PhAC biodegradation was reviewed. Impact of transformation products & operational conditions discussed. MBBR represent a promising technology for DCF and macrolides. Constructed wetlands are interesting as an effluent polishing step. Further toxicity assessment of metabolites and cost-benefit analyses needed. Abstract: Wastewater effluent discharges have been considered as one of the main sources of synthetic chemicals entering into the aquatic environment. Even though they occur at low concentrations, pharmaceutically active compounds (PhACs) can have an impact on ecological toxicity that affects aquatic organisms. Moreover, new regulations in development toward preserving water quality reinforces the increasing need to monitor and abate some PhACs in wastewater treatment plants (WWTPs), where they are typically only partially eliminated. Unlike most previous reviews, we have focussed on how the main biological and chemical molecular factors impact the biotransformations of key PhACs in biological WWTP processes. Biotransformations have been found to be an important contributor towards the removal of PhACs from WWTP effluents. This review paper critically assesses these aspects and the recent advances that have been achieved in wastewater treatment processes for biodegradation of 7 PhACs; namely the non-steroidal anti-inflammatory drug (NSAID) diclofenac (DCF); the macrolide antibiotics azithromycin (AZM), erythromycin (ERY) and clarithromycin (CLR); the two natural estrogens estrone (E1) and 17β-estradiol (E2), and the synthetic estrogen 17α-ethinylesradiol (EE2). These represent the micropollutants of the EU Watch list in Decision 2015/495/EU that are most relevant to WWTPs due to their frequent detection. The metabolic pathways, transformation products and impact of relevant factors to biological WWTP processes is addressed in this review. The biokinetics of PhAC biodegradation in different engineered bioprocesses is also discussed. Promising technologies and operational strategies that are likely to have a high impact on controlling PhAC releases are highlighted and future research needs are also proposed. Graphical abstract: Image, graphical abstract